Comparison of gastric-cancer radiotherapy performed with volumetric modulated arc therapy or single-field uniform-dose proton therapy. (4th May 2017) - Mondlane, Gracinda; Gubanski, Michael; Lind, Pehr A.; Ureba, Ana; Siegbahn, Albert
Abstract: Background: Proton-beam therapy of large abdominal cancers has been questioned due to the large variations in tissue density in the abdomen. The aim of this study was to evaluate the importance of these variations for the dose distributions produced in adjuvant radiotherapy of gastric cancer (GC), implemented with photon-based volumetric modulated arc therapy (VMAT) or with proton-beam single-field uniform-dose (SFUD) method. Material and methods: Eight GC patients were included in this study. For each patient, a VMAT- and an SFUD-plan were created. The prescription dose was 45 Gy (IsoE) given in 25 fractions. The plans were prepared on the original CT studies and the doses were thereafter recalculated on two modified CT studies (one with extra water filling and the other with expanded abdominal air-cavity volumes). Results: Compared to the original VMAT plans, the SFUD plans resulted in reduced median values for the V18 of the left kidney (26%), the liver mean dose (14.8 Gy (IsoE)) and the maximum dose given to the spinal cord (26.6 Gy (IsoE)). However, the PTV coverage decreased when the SFUD plans were recalculated on CT sets with extra air- (86%) and water-filling (87%). The added water filling only led to minor dosimetric changes for the OARs, but the extra air caused significant increases of the median values of V18 for the right and left kidneys (10% and 12%, respectively) and of V10 for the liver (12%). The density changes influenced the dose distributions in the VMAT plans to a minor extent. Conclusions: SFUD was found to be superior to VMAT for the plans prepared on the original CT sets. However, SFUD was inferior to VMAT for the modified CT sets.